Variationsrechnung: 11.7. bis 17.7.1982 - Frehse, Jens; Jäger, Willi; Tomi, Friedrich (Tagungsbericht, 1982)
H. Amann, Zürich; C. Gerhardt, Heidelberg; R. Böhme, Bochum-Querenburg; M. Giaquinta, Firenze; G. Dziuk, Aachen; E. Giusti, Firenze; K. Ecker, Heidelberg; M. Grüter, Düsseldorf; J. Frehse, Bonn; C. H. Gu, Shanghai; R. Finn, Stanford; R. Gulliver, Minneapolis; E. Heinz, Göttingen; H. Kaul, Tübingen; R. Hempel, München; M. Kucera, Prague; S. Hildebrandt, Bonn; R. Landes, Bayreuth; E. Hölder, Mainz; L. Lemaire, Bruxelles; H. S. Hu, Shanghaii; S. Luckhaus, Heidelberg; W. Jäger, Heidelberg; M. Meier, Bonn; J. Jost, Bonn; J. C. C. Nitsche, Minneapolis; D. Philipps, Evanson; K. Steffen, Düsseldorf; P. Rabinowitz, Madison; G. Ströhmer, Aachen; F. Sauvigny, Aachen; M. Struwe, Bonn; K. Schüffler, Düsseldorf; U. Thiel, Saarbrücken; C. G. Simader, Bayreuth; P. Tolksdorf, Bonn; L. Simon, Canberra; F. Tomi, Saarbrücken; E. Sperner, Bonn; A. J. Tromba, Santa Cruz; A. Visintin, Heidelberg; M. Wiegner, Bayreuth; M. v. Wahl, Bayreuth; E. Wienholtz, München